(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2020)
Introduction: In December, 2019, coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in Wuhan, China and has spread to Kenya with the first case being confirmed on 13th March 20201. By the end of June 2020, there were about 6000 confirmed cases in Kenya, with 143 deaths1. Currently, there are no statistics regarding pregnant women infected with COVID-19. Standard policies and precautions for facilities and personnel to safely care for COVID-19 patients as outlined in CDC and WHO guidelines have been adopted locally2,3. The facilities have also formulated creation of standard operating procedures to manage these patients e.g. operating separate labor and delivery units for COVID-positive patients and limiting the number of people in the delivery room, increased communication between neonatal and obstetric teams, limiting staff exposure and staff training on personal protective equipment procedures3. Kenyatta University Teaching, Referral and Research Hospital (KUTRRH) has been identified as one of the facilities designated for managing COVID-19 cases in Kenya (Figure 1). KUTRRH, established in 2019 is the third National Referral Hospital in Kenya with a 650 bed capacity and equipped with state-of-art medical amenities including eight negative pressure theatres, 24 bed capacity ICU and 12 bed HDU with a designated COVID 19 theatre4. Staff in all areas have been trained about the use of PPE and correct donning and doffing techniques. In order to minimize staff exposure, and therefore infection, only essential staff are present in the delivery rooms and theatres (Figures 2-5).